Development of Secured Memory Efficient Cloning Detection Protocol in WSNS Using RSA Algorithm - Pranav Pradip Chippalkatti, Swagat Madhav Karve, Rajesh Maharudra Patil, Nagaraja (Mathematical Statistician and Engineering Applications, 2021)
This paper is related to the developing an improvised of secured memory efficient cloning detection protocol in WSNs using RSA Algorithm and is used for efficient transfer of data packets with security. NS2 is used as the simulation tool to simulate the outputs. The main aim or objective of the proposed work presented in this paper is to develop a secured memory efficient cloning detection protocol in the mobile adhoc wireless sensor networks. The simulation results shows the effectivity of the methodology that is being proposed by us.